2013
DOI: 10.1007/s11356-013-2094-y
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Daphnia sp. acute toxicity test: miniaturization and prolongation for the testing of nanomaterials

Abstract: Manufacturing of nanomaterials (NMs) is often complex and expensive, and their environmental risks are poorly understood or even unknown. An economization of testing NMs is therefore desirable, which can be achieved by miniaturizing test systems. However, the downsizing of test vessels and volumes can enlarge the surface/volume ratio (SVR) which in turn can affect the bioavailable concentration of adsorbing substances like NMs. The present study focused on the miniaturization of the acute toxicity test with Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…In agreement with a study on nanoparticle toxicity (Dabrunz et al, 2011), immobilsation exceeding 10% was not observed within the recommended exposure time of 48 h (OECD guideline 202), but after 72 and 96 h. The pronounced increase in toxicity if exposure time is prolonged to 96 h is similar to another study (Baumann et al, 2014) and underlines the need for adaptations and different testing procedures on impacts of particles in general and microplastics in particular.…”
Section: Dose and Time Effects For 1-mm Pe-particlessupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with a study on nanoparticle toxicity (Dabrunz et al, 2011), immobilsation exceeding 10% was not observed within the recommended exposure time of 48 h (OECD guideline 202), but after 72 and 96 h. The pronounced increase in toxicity if exposure time is prolonged to 96 h is similar to another study (Baumann et al, 2014) and underlines the need for adaptations and different testing procedures on impacts of particles in general and microplastics in particular.…”
Section: Dose and Time Effects For 1-mm Pe-particlessupporting
confidence: 90%
“…Like suggested in literature for testing of particulate material (e.g. Baumann et al, 2014), exposure length was prolonged from 48 to 96 h in all treatments. Pre-tests confirmed that neonates from our culture younger than 24 h survive for 96 h in the absence of food without showing immobilisation or abnormal behaviour like being trapped at the water surface.…”
Section: Exposure Of D Magnamentioning
confidence: 96%
“…Comparison of 48 h and 96 h LC 50 values indicated a strong time dependence of toxicity, as has been previously suggested in a study assessing the acute toxicity of polyethylene microspheres to D. magna (Rehse et al, 2016). A similar observation was also made in a study investigating the acute exposure effects of nanomaterials to D. magna (Baumann et al, 2014). The marked increase in toxicity when the exposure time is prolonged to 96 h highlights the need for modifications of existing testing standards, which normally stipulate 48 h of exposure for acute toxicity assays (Rehse et al, 2016).…”
Section: Discussionsupporting
confidence: 78%
“…For detAgNP in the same medium, colloidal instability and increasing agglomerate size as well as relatively stable small aggregates of about 60 nm size have been reported (Baumann et al, 2014b;Cupi et al, 2015;unpublished data). In the present study, agglomerate sizes were constant, but a bit larger than reported for the stable dispersions.…”
Section: Discussionmentioning
confidence: 71%